China - Flower, Kathy (London, Great Britain : Kuperard ; New York, New York : Distributed in the U.S. and Canada by Random House Distribution Services, 2010)
Culture Smart! provides priceless nuggets of cultural information on China not found in a standard guidebook. Whether you are looking to secure a business deal, enrich your travels, or simply better understand China, its people and customs, Culture Smart! provides the information in a clear and highly readable guide.
Map of China -- Introduction -- Key facts -- Land And People: -- Terrain and climate -- China: a brief history -- Growth of new cities -- Han Chinese and minority nationalities -- Government and politics -- Thorny issues: Media, free speech, and human rights -- Environment -- Hong Kong, Taiwan, and Macau -- Overseas Chinese, and China's influence on its neighbors -- Values And Attitudes: -- Chinese philosophy -- Yin and Yang -- Feng Shui -- Pragmatism -- Citizens of the Middle Kingdom -- Attitudes to overseas Chinese -- Patience is a virtue -- Losing face -- Men and women -- Attitudes to women -- Myth of Chinese inscrutability -- Family -- Babies and children -- Respect for old age and ancestors -- Education -- Guangxi, or social networking Chinese style -- Chinese At Home: -- Lifestyles and housing -- Social relations and occupations -- Presents -- Chinese names -- Overcoming the language barrier -- Meeting and greeting -- Body language -- Exits and entrances -- Boy meets girl -- Hobbies -- Religion, Festivals, And Rituals: -- Many religions and none -- Traditional festivals and national holidays -- Birthdays, weddings, and funerals -- Health And Well-Being: -- Staying healthy in China -- Chinese medicine -- Beliefs about health -- Oigong and the martial arts -- Bathroom hygiene -- Food And Drink: -- Importance of food in Chinese culture -- Different regional cuisines -- Jasmine tea and hot rice wine -- Teahouse tranquility -- Smokers' paradise -- Time Out: -- Getting around -- Rules and regulations -- Money and safety -- Shopping -- Nightlife -- Culture -- Banquets And Entertaining: -- Good guest -- Greetings -- Seating and table arrangements -- Eating -- Making speeches and proposing toasts -- Making polite conversation -- Return match -- Business Briefing: -- China's entry to the World Trade Organization -- Business culture -- Contacting people -- Negotiating techniques -- Work in China -- Communicating: -- Mandarin, Cantonese, and other forms of Chinese -- Pinyin: the Romanization of Chinese characters -- Written Chinese-- Calligraphy -- Appendix: Simple vocabulary -- Further reading -- Index.
Includes bibliographical references (page 165) and index.
Keywords: Etiquette -- China; National characteristics, Chinese; China -- Social life and customs -- 2002-; China -- Civilization -- 2002-; China -- Guidebooks